Martinotti Cells: Community Organizers - Lee, Christine K. (2011)
The specificity of connections made by inhibitory interneurons in the neocortex is not well understood. In this issue of Neuron, Fino and Yuste use an enhanced version of two-photon glutamate uncaging, which preserves inhibitory synaptic transmission, to demonstrate that somatostatin-positive interneurons form densely convergent connections onto pyramidal cells in layer 2/3 of mouse frontal cortex.